Effects of bergapten on the pharmacokinetics of macitentan in rats both in vitro and in vivo - Xu, Jia; Zhou, Quan; Hou, Pengjiao; Wang, Yu; Geng, Peiwu; Lu, Zebei; Zhou, Yunfang; Dai, Dapeng; Wang, Shuanghu (Frontiers in Pharmacology, 2023)
Macitentan was approved by the United States Food and Drug Administration (FDA) in 2013 for the treatment of pulmonary arterial hypertension (PAH). Bergapten is a furanocoumarin that is abundant in Umbelliferae and Rutaceae plants and is widely used in many Chinese medicine prescriptions. Considering the possible combination of these two compounds, this study is aimed to investigate the effects of bergapten on the pharmacokinetics of macitentan both in vitro and in vivo. Rat liver microsomes (RLMs), human liver microsomes (HLMs), and recombinant human CYP3A4 (rCYP3A4) were used to investigate the inhibitory effects and mechanisms of bergapten on macitentan in vitro. In addition, pharmacokinetic parameters were also studied in vivo. Rats were randomly divided into two groups (six rats per group), with or without bergapten (10 mg/kg), and pretreated for 7 d. An oral dose of 20 mg/kg macitentan was administered to each group 30 min after bergapten or 0.5% CMC-Na administration on day 7. Blood was collected from the tail veins, and the plasma concentrations of macitentan and its metabolites were assessed by ultraperformance liquid chromatography -tandem mass spectrometer (UPLC-MS/MS). Finally, we analyzed the binding force of the enzyme and two small ligands by in silico molecular docking to verify the inhibitory effects of bergapten on macitentan. The in vitro results revealed that the IC50 values for RLMs, HLMs, and rCYP3A4 were 3.84 μM, 17.82 μM and 12.81 μM, respectively. In vivo pharmacokinetic experiments showed that the AUC(0-t), AUC(0-∞), and Cmax of macitentan in the experimental group (20263.67μg/L*h, 20378.31μg/L*h and 2999.69μg/L, respectively) increased significantly compared with the control group (7873.97μg/L*h, 7897.83μg/L*h and 1339.44μg/L, respectively), while the CLz/F (1.07L/h/kg) of macitentan and the metabolite-parent ratio (MR) displayed a significant decrease. Bergapten competitively inhibited macitentan metabolism in vitro and altered its pharmacokinetic characteristics in vivo. Further molecular docking analysis was also consistent with the experimental results. This study provides a reference for the combined use of bergapten and macitentan in clinical practice.